PROBIOTICS VS. BACTERIA: HOW LACTOBACILLUS CASEI BATTLES STREPTOCOCCUS MUTANS BIOFILM (IN VITRO) - Praptiningsih, Rahmawati Sri; Sari, Rina Kartika; Ikhsandarujati, Renanda Rifki; Putranto, Rama (Jurnal Medali, 2025)
Background:Caries formation is influenced by several factors such as teeth, microorganisms, biofilm, and also time. The initial bacteria that play an important role in biofilm formation is Streptococcus mutans. Probiotics made from these bacteria are considered capable of overcoming dental and oral health problems because they are able to suppress the biofilm which will coat and protect the mucosa from invasion by cariogenic bacteria such as caries.Purpose:To determine the effect of the probioticLactobacillus casei in reducing Streptococcus mutans biofilm growth (in vitro).Method:The research design carried out was experimental research with a post test only control group design. The research samples were divided into 3 groups, namely the chlorhexidine, distilled water and probiotic groups. Biofilm thickness testing was carried out by OD (Optical density) using an ELISA-reader. Parametric statistical test analysis using the Kruskal Wallis Test.Results:The results of the Kruskal Wallis statistical test showed P= 0.000 there is a significant difference in the 3 Streptococcus mutans thickness test groups.Conclusion:The probioticLactobacillus casei has the effect of reducing the thickness of the Streptococcus mutans biofilm